Liquid–liquid phase separation in hepatocellular carcinoma - Xu, Jianguo; Liu, Wangwang; Yao, Yihan; Knowles, Tuomas P. J.; Zhang, Zhi-Gang; Zhang, Yan-Li (Frontiers in Cell and Developmental Biology, 2024)
Liquid-liquid phase separation (LLPS) drives the formation of membraneless intracellular compartments within both cytoplasm and nucleus. These compartments can form distinct physicochemical environments, and in particular display different concentrations of proteins, RNA, and macromolecules compared to the surrounding cytosol. Recent studies have highlighted the significant role of aberrant LLPS in cancer development and progression, impacting many core processes such as oncogenic signalling pathways, transcriptional dysregulation, and genome instability. In hepatocellular carcinoma (HCC), aberrant formation of biomolecular condensates has been observed in a number of preclinical models, highlighting their significance as an emerging factor in understanding cancer biology and its molecular underpinnings. In this review, we summarize emerging evidence and recent advances in understanding the role of LLPS in HCC, with a particular focus on the regulation and dysregulation of cytoplasmic and nuclear condensates in cancer cells. We finally discuss how an emerging understanding of phase separation processes in HCC opens up new potential treatment avenues.